ANALISIS PEMBERDAYAAN PENERIMA MANFAAT PROGRAM ETOS ID DI LEMBAGA PENGEMBANGAN INSANI DOMPET DHUAFA - Anggraeni, Sri; Muhtadi, Muhtadi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Abstract: Poverty is a complex problem that involves several factors such as education level, income, lack of knowledge and skills and human resources, so that children born to poor families are likely to have lower levels of education and they tend to work in low-income sectors. This study aims to determine the implementation of the Etos ID program and determine the results of empowerment in the Etos ID program. This study used a qualitative approach, in collecting informants the researcher used a purposive sampling technique, data collection was carried out by means of observation, interviews and documentation, data analysis techniques used data analysis techniques proposed by Miles and Huberman, and data validity techniques used source triangulation. The research results obtained show that in carrying out empowerment in the ID Etos (Improvement and Development) program, LPI DD carries out several stages including the preparation stage, the assessment or assessment stage, the alternative program or activity planning stage, the action plan formulation stage, the program or activity implementation stage, evaluation stage and termination stage. The results of empowerment in the Etos ID program in the economic, educational, health, spiritual, technological and political fields were considered optimal.Keywords: Empowerment; Benefit recipients; Scholarship.Abstrak: Kemiskinan adalah masalah kompleks yang melibatkan beberapa faktor seperti tingkat pendidikan, pendapatan, kurangnya pengetahuan dan keterampilan serta SDM, sehingga anak yang terlahir dari keluarga miskin berpeluang memiliki tingkat pendidikan yang lebih rendah dan mereka cenderung bekerja di sektor yang berpenghasilan rendah. Penelitian ini bertujuan untuk mengetahui pelaksanaan program Etos ID dan mengetahui hasil pemberdayaan pada program Etos ID. Penelitian ini menggunakan pendekatan kualitatif, dalam pengambilan informan peneliti menggunakan teknik purposive sampling, pengambilan data dilakukan dengan cara observasi, wawancara dan dokumentasi, teknik analisis data menggunakan teknik analisis data yang dikemukakan oleh Miles dan Huberman, dan teknik keabsahan data menggunakan triangulasi sumber. Hasil penelitian yang didapatkan menunjukan bahwa dalam melaksanakan pemberdayaan pada program Etos ID (Improvement and Development), LPI DD menjalankan beberapa tahapan di antaranya tahap persiapan, tahap pengkajian atau assessment, tahap perencanaan alternatif program atau kegiatan, tahap pemformulasian rencana aksi, tahap pelaksanaan program atau kegiatan, tahap evaluasi dan tahap terminasi. Hasil pemberdayaan pada program Etos ID di bidang ekonomi, pendidikan, kesehatan, spiritual, teknologi dan politik dinilai maksimal.Kata Kunci: Pemberdayaan; Penerima Manfaat; Beasiswa.